COMPARATIVE STUDY WITH CARD MEDIA ON LEARNING OUTCOMES IN CHEMICAL BONDING MATERIALS AT SMA NEGERI 1 PEUSANGAN - Riska Imanda; Fakhrah Fakhrah; Cut Maria Ulfa (Universitas Lampung, 2021)
Abstract: This study aims to see the comparison of learning outcomes between TGT type learning models with STAD type learning models with STAD type learning models equipped with question card media. Comparative causal research types with causal pattern design. The sampling technique in this study used purposive sampling. The sample in this study is class X IPA 1 as an experimental class 1 that applies the TGT learning model and X IPA 3 as an experimental class 2 that applies the STAD learning model, each class totaling 24 students. Based on the results of data analysis, the average value of cognitive learning outcomes in the pretest-posttest in experimental class 1 was 38,33 and 75,42, while the average value of cognitive learning outcomes in the pretest-posttest in experimental class 2 was 34,17 and 69,79. T-test was carried out using independent sample test assisted with SPSS 17.0 software and obtained a significant value (2-tailed) of 0,03 0,05, it means that H0 is rejected and Ha is accepted. Based on the results of the study it can be concluded that there is a comparison of learning outcomes of students who use the TGT and STAD learning model with a question card media on chemical bonding material.Keywords: Card words, Learning outcomes, Ikatan Kimia, STAD, TGT. DOI: 10.23960/jppk.v10.i3.2021.06